Computer-assisted learning of Croatian language stress system (CAL-CROLESS) - Mikelić, Nives; Lauc, Tomislava; Golubić, Kruno (2005)
The aim of the paper is to present the computer-assisted learning of Croatian language stress system as a base for the development of the computer-assisted Croatian ortography learning system. The system includes two main modules: the dictionary and the rule list for stress assignment and stress realization in Croatian. It is possible to use it for knowledge pretesting, learning and final testing of the acquired knowledge. Two different learning approaches were taken: one was based on acquiring the knowledge concerning the word-stress patterns that determine the word-stress assignment, and the other was sample-based learning. The goal was to probe the fruitfulness of both methods for dealing with a stress assignment problem for Croatian.
Projekt MZOS
ENG